Photodegradation of soluble and emulsive cutting fluids using TiO 2 as catalyst - Araújo, Adriana B. [UNESP]; Amarante Jr., Ozelito P.; Vieira, Eny M.; Valente, José P. S. [UNESP]; Padilha, Pedro M. [UNESP]; Florentino, Ariovaldo O. [UNESP] (FapUNIFESP (SciELO), 2006)
This paper describes results of the photo-degradation of three types of soluble and emulsive cutting fluids in an aqueous medium, using TiO2 as catalyst in suspension and UV radiation. The TiO2 proved to be an effective catalyst for the degradation of the cutting fluids investigated. The degradation rate depends on pH and nature of the fluids. The best performance of catalyst was observed at pH 8.0 for all the fluids when most of 70% of the organic load was decomposed. ©2006 Sociedade Brasileira de Química.
Keywords: Aqueous effluents; Machining lubricants; Photocatalysis